A Comprehensive Review of Water Quality Assessment Through Physical and Chemical Parameters (Journal of Advances and Scholarly Researches in Allied Education, 2022)
Water quality assessment is crucial for ensuring the sustainability of aquatic ecosystems and public health. This review paper provides a comprehensive analysis of the methodologies and significance of evaluating water quality through physical and chemical parameters. Key parameters such as temperature, pH, dissolved oxygen, turbidity, total dissolved solids, and various chemical contaminants, including heavy metals and nutrients, are examined in detail. The paper discusses the standard procedures for measuring these parameters and their implications for water quality. Additionally, it highlights the influence of anthropogenic activities and natural processes on these indicators. By synthesizing recent research findings, this review aims to offer a thorough understanding of the current practices in water quality assessment, identify gaps in knowledge, and propose areas for future research. This paper serves as a valuable resource for researchers, policymakers, and environmental managers dedicated to maintaining and improving water quality.